Report a Crime as a Causes of non-responsibility In Iraqi criminal law - Assistant Lecturer: Khaldoon Ahmed Mohammed (The college of law and political science journal, 2024)
Informing about the crime and its perpetrators is a national and moral duty imposed by laws and moral principles, and it has a noble goal, which is the individual’s cooperation with the authority in combating the crime, uncovering its cover, identifying its perpetrators, or limiting its spread at the very least.The subject of the news has sparked a wide legislative and jurisprudential controversy in criminal law, due to conflicting legal rulings and differences in jurisprudential opinions, regarding it as one of the reasons for permissibility. Therefore, we will try to analyze the legal texts and refer to jurisprudential opinions by making use of these jurisprudential opinions and stating the most correct opinion among them.